ANALISIS MOTIVASI, KEPUASAN KERJA DAN KOMITMEN TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA PT BANK RAKYAT INDONESIA CABANG STABAT - Ramandha; Batu Bara, Soulthan; Ahmad, Rizal (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The research analysis aims to determine the influence of motivation, job satisfaction and commitment on work productivity at PT Bank Rakyat Indonesia Stabat Branch. The data analysis technique used is an associative research method with the help of the SPSS version 25 program. This research uses multiple linear regression analysis. The sample in this study was 45 respondents. Primary data collection uses a questionnaire. The results of the research show that the t value is 8.749 > t table of 2.01 with a significant value of 0.00 < 0.05, so the hypothesis H1 is rejected and H0 is accepted, meaning that motivation has a partially significant effect on employee work productivity at PT Bank Rakyat Indonesia Stabat Branch . The test results for the job satisfaction variable show a tcount value of 4.173 > ttable of 2.01 with a significant value of 0.00 <0.05, so the hypothesis H2 is accepted and H0 is rejected, meaning that job satisfaction has a partially positive and significant effect on employee work productivity in PT Bank Rakyat Indonesia Stabat Branch. The test results for the commitment variable show a tcount value of 7.257 > ttable of 2.01 with a significant value of 0.00 <0.05, so hypothesis H3 is accepted and H0 is rejected, meaning that commitment has a partially positive and significant effect on employee work productivity at PT Bank Indonesian People, Stabat Branch. The result of the calculated F is 186.264 which is greater than 2.83 and the significant value of 0.000 is smaller than 0.05 so it can be concluded that hypothesis 4 is accepted and hypothesis 0 is rejected so it can be concluded that motivation, job satisfaction and commitment have a significant effect simultaneously on employee work productivity at PT Bank Rakyat Indonesia Stabat Branch..